2007
DOI: 10.1039/b711083a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen abstraction from deoxyribose by a neighbouring uracil-5-yl radical

Abstract: Hydrogen abstraction from the C1' and C2' positions of deoxyadenosine by a neighbouring uracil-5-yl radical in the 5'-AU*-3' DNA sequence is explored using DFT. This hydrogen abstraction is the first step in a sequence leading to single or double strand break in DNA. The uracil-5-yl radical can be the result of photolysis or low-energy electron (LEE) attachment. If the radical is produced by photolysis the neighbouring adenine will become a cation radical and if it is produced by LEE the adenine will remain ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 28 publications
(35 reference statements)
1
31
1
Order By: Relevance
“…[26][27][28] This process shows a resonance at very low electron energies (< 2.0 eV) indicating that it occurs by DEA. 35,36 Similar results are obtained for 5BrU in the condensed phase. 29,30 The loss of Br ions from T5BrUT may be explained by the initial formation of a transient molecular ion followed DEA in which the negative charge goes to Br.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…[26][27][28] This process shows a resonance at very low electron energies (< 2.0 eV) indicating that it occurs by DEA. 35,36 Similar results are obtained for 5BrU in the condensed phase. 29,30 The loss of Br ions from T5BrUT may be explained by the initial formation of a transient molecular ion followed DEA in which the negative charge goes to Br.…”
Section: Resultssupporting
confidence: 76%
“…According to theoretical studies, C-Br cleavage is the lowest energy process (about 1.88 kcal/mol) 31 whereas the energy for C-O bond cleavage and C-N bond cleavage are higher by at least 3-fold and 10-fold, respectively. 34,35 Interestingly, the yield of damage by these three pathways is inversely proportional to the distance between the nucleobase moiety and the bond undergoing cleavage, i.e., the farther away from the nucleobase, the lower the yield of damage. Similarly, the lack of damage at sites next to abasic sites in short oligonucleotides may be attributed to initial capture of LEEs by the nucleobase and subsequent transfer to other positions of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The latter radical is formed via hydrogen atom transfer from the 2′ site of 5′-neighbouring sugar to the uracil/cytosine radical (this uracil/cytosine radical is a product of the primary dissociative electron attachment (DEA) process). 36 The formation of dTI in the current studies and no evidence for dTBr formation in the previous one 10 may be explained by the difference in masses between the iodide and bromide anions. Probably, the dT radical cation forms before the heavier iodide leaves the reaction centre while the lighter bromide anion moves too far, in the time needed for the formation of the dT cation radical, to interact with it effectively (forming dTBr).…”
Section: Resultscontrasting
confidence: 55%
“…8 A key process, that ultimately results in DNA strand-cleavage, involves uracil-5-yl radicals abstracting H atoms from nearby functional groups. 9,10 Alternatively, several studies have investigated the possibility that, under aerobic conditions, reaction of the uracil-5-yl radicals with molecular oxygen will form peroxyl radical intermediates (Scheme 1 (i)), and that these peroxyl radicals might be key intermediates in rationalising the activity of these halouracils. 11,12 Following this line of enquiry, Schyman et al reported in a computational study that the peroxyl radical would actually be a less efficient at H atom abstraction from deoxyribose than the uracil-5-yl parent.…”
Section: Introductionmentioning
confidence: 99%